Layer-by-Layer Assembly of Polysaccharides and 6,10-Ionene for Separation of Nitrogen-Containing Pharmaceuticals and Their Enantiorecognition by Capillary Electrophoresis - Anna Ioutsi; Elena Shapovalova; Aleksandra Prokhorova; Oleg Shpigun (Journal of Chemistry)
Two silica capillaries modified layer-by-layer with 6,10-ionene and N-(3-sulfo-3-carboxy)-propionylchitosan (SCPC) and with 6,10-ionene and dextran sulfate (DS) were prepared and investigated. Dynamic coating of the capillary efficiently reduces the adsorption of the background electrolyte, sample matrix components, and analytes on its inner wall. Such coatings effect good reproducibility and sensitivity of determination. We demonstrate that separation of betablockers, calcium channel blockers, alpha-adrenergic agonists, H1-blockers, and diuretics was the most efficient and rapid separation with a capillary modified with dextran sulfate. Tetrahydrozoline, carbinoxamine, and furacilin, which are commonly employed as treatments for allergic rhinitis, were identified in human urea. Their concentrations, independently verified by HPLC, were found to be 5.3±0.8, 6.6±0.5, and 0.9±0.2 μg mL−1, with LOD=0.07, 0.03, 0.10 μg mL−1, and LOQ=1.0, 0.8, 0.6 μg mL−1, respectively.